2018
DOI: 10.1111/ijfs.13758
|View full text |Cite
|
Sign up to set email alerts
|

Quality, sensory and volatile profiles of fresh‐cut big top nectarines cold stored in air or modified atmosphere packaging

Abstract: Summary Solid‐phase microextraction (SPME) GC‐MS was used to investigate the volatile organic compound (VOC) profile of fresh‐cut ‘Big Top’ nectarine samples, stored in unsealed bags (AIR) or packed in active modified atmosphere (MAP) after 8 days of cold storage. Nectarine slices were also subjected to sensory and quality analysis after harvest and at the end of the storage. MAP preserved the overall quality, the appearance and the olfactory properties of nectarine slices during storage, while AIR samples sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Methyl decanoate and benzyl butanoate were present in relatively low amounts (average content <1.5% TIC) in the FPs of each variety. Consistent with previous reports [ 47 , 48 ], ethyl tiglate was the most abundant in most of the WFs of the cultivars analyzed in this study.…”
Section: Resultssupporting
confidence: 93%
“…Methyl decanoate and benzyl butanoate were present in relatively low amounts (average content <1.5% TIC) in the FPs of each variety. Consistent with previous reports [ 47 , 48 ], ethyl tiglate was the most abundant in most of the WFs of the cultivars analyzed in this study.…”
Section: Resultssupporting
confidence: 93%
“…The villi of all treatment group samples gradually disappeared and were invisible to the naked eye, resulting in smooth fruit (Hashemi, ). A comprehensive evaluation indicated that the Ethylene‐L treatment more effectively preserved the flavor, taste, appearance, and feel of peaches, as well as other sensory indicators (Cozzolino et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have been performed to reduce CI symptoms during the storage of fresh-cut peaches and nectarines at low temperatures in order to avoid postharvest losses. Most of them have focused on the appropriateness of different varieties [13,14], the use of short-term heat treatments [15], the application of edible coatings [16,17], the enzymatic inactivation by high hydrostatic pressure processing [14,18], the effects of storage temperature and the implementation of modified atmosphere packaging (MAP) [15,19]. Storage temperature can significantly affect the respiration and the browning rate, the volatile profiles, the CI symptoms and the overall quality of fresh-cut nectarines, extending or reducing their shelf-life [4,17].…”
Section: Introductionmentioning
confidence: 99%
“…Storage temperature can significantly affect the respiration and the browning rate, the volatile profiles, the CI symptoms and the overall quality of fresh-cut nectarines, extending or reducing their shelf-life [4,17]. Specifically, Cozzolino et al (2018) [19] evaluated the qualitative, the sensory and the volatile profiles of fresh and fresh-cut 'Big Top' nectarine slices stored at 4 • C for 8 days in active MAP or air, demonstrating that MAP preserved the overall quality throughout the storage period. Indeed, a panel of trained judges discriminated nectarine slices cold-stored in air and MAP after 8 days mostly based on visual and olfactory properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation